Evaluation of an electricity-independent method for IS2404 Loop-mediated isothermal amplification (LAMP) diagnosis of Buruli ulcer in resource-limited settings. - Evans K Ahortor; Theresa Manful Gwira; Samiratu Mahazu; Astrid C Erber; Anthony Ablordey (Public Library of Science (PLoS), 2024)
Introduction Buruli ulcer (BU) caused by Mycobacterium ulcerans (MU) is a devastating necrotic skin disease. PCR, recommended for confirmation of BU by WHO, requires an adequately equipped laboratory, therefore often delaying timely diagnosis and treatment of BU patients in remote settings. Loop-mediated isothermal amplification (LAMP) is a PCR-based protocol for isothermal amplification of DNA that has been suggested for diagnosis of BU in low-resource settings. Study aims and methods This is an exploratory diagnostic test evaluation study, with an embedded qualitative sub-study. Its aims are two-fold: First, to evaluate a simple rapid syringe-based DNA extraction method (SM) in comparison with a more elaborate conventional DNA extraction method (CM), followed by a LAMP assay targeting IS2404 for the detection of MU, either using a commercially available pocket warmer (pw) or a heat block (hb) for incubation. Second, to complement this by exploring the diagnostic workflow for BU at a community-based health centre in an endemic area in rural Ghana as an example of a potential target setting, using interviews with researchers and health care workers (HCWs). Diagnostic test evaluation results are discussed in relation to the requirements of a target product profile (TPP) for BU diagnosis and the target setting. Results A protocol using SM for DNA extraction followed by IS2404 PCR (IS2404 PCRSM) was able to identify MU DNA in 73 out of 83 BU clinical specimens submitted for diagnosis. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of IS2404 PCRSM were 90.12%, 100%, 100% and 65.21% respectively, as compared to the reference standard IS2404 PCR in combination with a standard extraction protocol for mycobacterial DNA. Evaluation of the LAMP assay on 64 SM DNA extracts showed a sensitivity, specificity, PPV and NPV of 83.6%, 100%, 100% and 50%, respectively, using either pocket warmer (pwLAMPSM) or heat block (hbLAMPSM) for incubation of the reaction, as compared to the same reference standard. The limit of detection of pwLAMPSM was found to be 30 copies of the IS2404 target. Interview findings explored barriers to BU diagnosis and treatment, including perceptions of the disease, costs, and availability of transport. Participants confirmed that a diagnosis at the PoC, in addition to screening based on clinical criteria, would be advantageous in order to prevent delays and loss to follow-up. Discussion and conclusions The high diagnostic and analytic accuracy of the pwLAMP, evaluated by us in combination with a syringe-based DNA extraction method, supports its potential use for the rapid detection of MU in suspected BU samples at the community or primary health care level without reliable electricity supply. Further optimization needs include a lysis buffer, evaluation directly at the PoC and/or other sites, assessing staff training requirements and quality control.